What Is My Next Step? School Students' Perceptions of Feedback - Brooks, Cameron; Huang, Yangtao; Hattie, John; Carroll, Annemaree; Burton, Rochelle (Frontiers in Education, 2019)
Feedback literature is dominated by claims of large effect sizes (Hattie, 2009) yet, there is remarkable levels of variability in the effects of feedback. The same feedback can be effective for one student but not another, and in one situation but not another. There is a need to better understand how students are receiving feedback and currently there is relatively little research on school students’ perceptions of feedback. This is in contrast to current social constructivist and self-regulatory models of feedback, which see the learner as an active agent in receiving, interpreting and applying feedback information. This paper aims to investigate school student perceptions of feedback and validate a student feedback perception questionnaire. The questionnaire was used to collect data about the helpfulness of different feedback types and levels to learning. Results demonstrated construct validity for the questionnaire and notably, students reported that feed forward (improvement based feedback) aimed at the task level was the most helpful. Implications for teaching and learning are discussed, in regard to how students receive feedback.